Angular analysis of B0d → K∗μ+μ− decays in pp collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2018)
An angular analysis of the decay B0d → K∗μ+μ− is presented, based on proton-proton collision data recorded by the ATLAS experiment at the LHC. The study is using 20.3 fb−1 of integrated luminosity collected during 2012 at centre-of-mass energy of √s = 8 TeV. Measurements of the K* longitudinal polarisation fraction and a set of angular parameters obtained for this decay are presented. The results are compatible with the Standard Model predictions.